2020
DOI: 10.3758/s13423-019-01708-4
|View full text |Cite
|
Sign up to set email alerts
|

Intonation does aid serial recall after all

Abstract: A sequence of spoken digits is easier to recall if the digits are grouped into smaller chunks (e.g., through the insertion of pauses). It has been claimed that intonation does not facilitate recall over and above the effect achieved by pauses. This may be related to the fact that past research has used synthesized intonation contours. In this replication study, we show that intonation does provide benefits once more naturalistic intonation contours are used. This benefit is independent of response modality (sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 21 publications
2
12
0
Order By: Relevance
“…The plot of recall by position also suggested a “mini-primacy” effect interrupting the smoothness of the primacy-recency curve in the grouped conditions, as has been seen in the literature ( Parmentier & Maybery, 2008 ; Savino et al, 2020 ). As before, this was investigated in a post-hoc test for the effect of condition at each position of the data, with a Bonferroni correction for 10 tests.…”
Section: Resultssupporting
confidence: 75%
See 2 more Smart Citations
“…The plot of recall by position also suggested a “mini-primacy” effect interrupting the smoothness of the primacy-recency curve in the grouped conditions, as has been seen in the literature ( Parmentier & Maybery, 2008 ; Savino et al, 2020 ). As before, this was investigated in a post-hoc test for the effect of condition at each position of the data, with a Bonferroni correction for 10 tests.…”
Section: Resultssupporting
confidence: 75%
“…He found that manipulating the mean fundamental frequency (F0) of different words, in and of itself, did not enhance recall; rather, it only helped when the F0 pattern suggested a grouping of the words (Frankish, 1989;1995). This grouping phenomenon has since been demonstrated using a number of characteristics of the auditory signal: pitch, timing, voice, stress, sound location-or even explicit instruction (Bower, 1970;Farrell, 2008;Farrell et al, 2011;Gilbert et al, 2014;Ng & Maybery, 2002;Parmentier & Maybery, 2008;Savino et al, 2014;Savino et al, 2020;Towse et al, 1999). As long as any of these characteristics indicate a grouping, recall is enhanced, and this grouping becomes a cue for memory.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it is likely that using a similar dual-task paradigm, degraded pitch information would increase the listening effort during speech decoding, leaving fewer resources for memorizing the items. In addition, there is some evidence that certain pitch patterns in spoken material (across words) can improve immediate free recall for NH listeners [31][32][33][34][35] . It is unclear whether such phenomena would hold with abnormal pitch patterns (within or across words) but this represents an additional route by which pitch degradations could impair the secondary task in a dual-task paradigm.…”
Section: Introductionmentioning
confidence: 99%
“…We compared a xed condition (identical to the monotonized condition of experiment 1) with a melodic condition, in which monotonized words were presented at different mean F0s ("notes"), making an arpeggio-like sequence of pitches. It was not known how this pitch pattern would affect recall, if at all: there are various studies showing pitch patterns to be either helpful, irrelevant, or even detrimental to short-term memory of words 31,32,34,35,[51][52][53] . These manipulations will help us understand whether access to salient pitch information supports word decoding and storage.…”
Section: Introductionmentioning
confidence: 99%